2016
DOI: 10.1021/acs.est.5b05905
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Alter the Properties and Sinking Rates of Zooplankton Faecal Pellets

Abstract: Plastic debris is a widespread contaminant, prevalent in aquatic ecosystems across the globe. Zooplankton readily ingest microscopic plastic (microplastic, < 1 mm), which are later egested within their faecal pellets. These pellets are a source of food for marine organisms, and contribute to the oceanic vertical flux of particulate organic matter as part of the biological pump. The effects of microplastics on faecal pellet properties are currently unknown. Here we test the hypotheses that (1) faecal pellets ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
296
4
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(316 citation statements)
references
References 61 publications
(152 reference statements)
8
296
4
8
Order By: Relevance
“…Such studies have prompted researchers to investigate the impact on ecosystem processes. Indeed, Cole et al (2016) found that microplastics alter the sinking rates of copepod faecal pellets if ingested and in consequence may affect the downward flux of carbon to the ocean floor. With the increasing evidence that microplastics represent an ecosystem and environmental health concern, UNEP and the EU Commission have established bodies and efforts to guide in decision making and legislation (Galgani et al, 2013;UNEP, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have prompted researchers to investigate the impact on ecosystem processes. Indeed, Cole et al (2016) found that microplastics alter the sinking rates of copepod faecal pellets if ingested and in consequence may affect the downward flux of carbon to the ocean floor. With the increasing evidence that microplastics represent an ecosystem and environmental health concern, UNEP and the EU Commission have established bodies and efforts to guide in decision making and legislation (Galgani et al, 2013;UNEP, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Timescales by which large objects are fragmented to microplastics by weathering-induced and biologically mediated processes, such as grinding in bird gizzards or biting by fishes (Kühn et al 2015), are not well constrained. Plastics that are initially buoyant may be transported to greater depth upon increased density caused by biofouling (Ye & Andrady 1991, Fazey & Ryan 2016, ingestion by vertically migrating species (Choy & Drazen 2013), or sinking within fecal pellets (Cole et al 2016) or marine aggregates (Long et al 2015). Some of these processes have been demonstrated in laboratory or field experiments, but their rates in the environment are unknown.…”
Section: Estimating Marine Terms In the Mass Balancementioning
confidence: 99%
“…For example, microplastics may become transported away from surface waters via encapsulation within fecal pellets [81]. Although this topic has not been investigated in freshwater or marine environments, the gut bacteria of mealworms (larvae of Tenebrio molitor Linnaeus) can degrade polystyrene [82], and certain aquatic organisms could harbor microorganisms capable of modifying the surface properties of plastics and/or biodegrading them.…”
Section: Interactions With Higher Organisms and The Wider Environmentmentioning
confidence: 99%